IS HIERARCHY RELATIVELY FIXED? - Wu, Maoguo (European Scientific Journal, ESJ, 2014)
This paper examines one main assumption of the tournament theory, i.e., hierarchy is relatively fixed. Using personnel records from a large British financial sector firm, this paper empirically tests to what extent hierarchy in the sample firm is fixed. Empirical tests find that external hiring number, promotion into level number, promotion out of level number, and exit number are closely related, and therefore argue that hierarchy is relatively fixed.